Experimental study of pyolysis gas combustion using oxygen carriers - Gracia Monforte, César; Ábrego, Javier; Gonzalo, Alberto; Arauzo, Jesús; Nafees, Mahnoor (Jornada de Jóvenes Investigadores del I3A, 2023)
In this work the oxidation of a pyrolysis gas is studied, using differents oxygen carriers at differents temperatures using Chemical Looping Combustion (CLC) technology.